Investigations on Optimum Size and Shape of Plots with Dalbergia sissoo (Roxb.) in Shiwalik Foothills - Agnihotri, Y.; Agarwal, M. C. (Indian Forester, 1995)
Investigations on the optimum size and shape of plots and their arrangement in blocks have been made with Dalbergia sissoo (Roxb.) at the Research Farm of the Central Soil and Water Conservation Research and Training Institute, Research Centre, Chandigarh situated in lower Ambala ShiwaIik foothills. Height and diameter (bh) observations of all the individual trees spaced at 2m Ã— 2m in 24 trees Ã— 24 trees compartment were recorded. Coefficient of variation (CV) of different sizes and shapes of plots and blocks were worked out and used for determination of optimum size and shape of plots and blocks. A plot having 8-12 trees was considered to be optimum size. Blocks in general, were found to be more efficient tban without blocking arrangements. Bigger blocks were less efficient than small blocks.